Gender on Board and the Impact to Firm Performance through Innovation as Mediating Variable: Evidence from Indonesian non-Financial Firms - Hasina, Zahwaril; Bernawati, Yustrida (University of Merdeka Malang, 2021)
This study examines the effect of gender on board on firm performance in Indonesia through innovation as mediation. The independent, dependent, and mediating variable used in this research is the gender of the board of directors, firm performance, and innovation. This analysis uses Indonesian non-financial firms that perform any innovation activities and are listed on the Indonesian Stock Exchange in 2009-2019 as our sample. The method used in this study is the quantitative method and processed by using SPSS tools to test the hypothesis. The results showed that gender onboard has no effect on firm performance directly but positively affects innovation. Meanwhile, innovation has a positive effect on firm performance. Then gender on board has a positive impact on the firm performance through innovation as the mediation variable. The novelty of this research is to add an innovation variable to clarify the effect of gender on board to the firm performance. This research can be used to consider companies and other policymakers to determine the board in the company.DOI : https://doi.org/10.26905/jkdp.v25i2.5462